Pengembangan Kewirausahaan Di SMA Negeri 1 Sunggal Kabupaten Deli Serdang Melalui Kegiatan Pelatihan Akuntansi - Dito Aditia Darma Nasution; Handriyani Dwilita; Vina Arnita (University of Islam Malang, 2019)
State Senior High School1 Sunggal Deli Serdang Regency, which has high quality studentshave a high enthusiasm in entrepreneurship so that the potential to be able to bring upsuccessful young entrepreneur. The success of coaching young people into entrepreneurswill increase regional scale economic prosperity in this case in Deli Serdang Regencyeven on a national scale (Indonesian). Activities carried out in this community serviceis in the form of accounting training activities for students of State Senior High School 1 Sunggal Deli SerdangRegency. The purpose of this activity is to develop entrepreneurship for studentsSenior High School 1 SunggalDeli Serdang Regency so that it becomes a successful young entrepreneur.The results of community service activities indicate an increase in knowledgeand accounting skills in entrepreneurship by Senior High School 1 Sunggal Deli Serdang Regency students